The bottom billion why the poorest countries are failing and what can be done about it - Collier, Paul. (Oxford ; New York : Oxford University Press, 2007)
Global poverty, economist Collier points out, is actually falling quite rapidly for about 80% of the world. The real crisis lies in a group of about 50 failing states, the bottom billion, whose problems defy traditional approaches to alleviating poverty. Here, Collier contends that these fifty failed states pose the central challenge of the developing world in the twenty-first century. This group of small nations, largely unnoticed by the industrialized West, are dropping further and further behind the majority of the world's people, often falling into an absolute decline in living standards. A struggle rages within each of these nation between reformers and corrupt leaders--and the corrupt are winning. Collier analyzes the causes of failure, and offers a bold new plan.--From publisher description.
Falling behind and falling apart : the bottom billion -- The conflict trap -- The natural resource trap -- Landlocked with bad neighbors -- Bad governance in a small country -- On missing the boat : the marginalization of the bottom billion in the world economy -- Aid to the rescue? -- Military intervention -- Laws and charters -- Trade policy for reversing marginalization -- An agenda for action.
Includes bibliographical references (p. [193]-195) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2023. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Poor -- Developing countries; Poverty -- Developing countries; Electronic books